Influence of Cultural Perspectives on Caregivers’ Approaches to Seeking Health Care for Mentally Ill Patients in Uasin Gishu County, Kenya - Caroline Atieno Ombok (Disease and Health Research: New Insights Vol. 11, 2024)
Cultural norms and regulations significantly influence the health-seeking behavior of caregivers of individuals with mental illness. These cultural beliefs shape perceptions of mental health, often affecting how caregivers choose treatment options for their loved ones. In many societies, mental illness is still heavily stigmatized, and in some cases, it is associated with spiritual or supernatural causes. As a result, caregivers may turn to culturally appropriate healthcare options, such as traditional healers, spiritual interventions, or herbal remedies, alongside or even in place of biomedical treatment [1]. Although hospitals and other formal healthcare institutions remain primary sources of care, the co-existence of these culturally rooted practices highlights the need for further research into their efficacy and integration into mainstream healthcare services. The purpose of this study was to examine the influence of cultural perspectives approaches on health-seeking behavior by caregivers of individuals with mental illness in Uasin Gishu County, Kenya. Specifically, the study aimed to understand how caregivers modify their behavior when seeking care, considering the strong presence of cultural norms in their communities. Uasin Gishu County is culturally diverse, with various communities adhering to different traditional practices that inform their approach to healthcare. These practices, particularly in mental health, offer an important area for research to better integrate culturally sensitive approaches into the broader healthcare system [2]. The study employed a contemporaneous mixed-methods design, combining both qualitative and quantitative approaches. This methodology allowed for a comprehensive analysis of the complex factors influencing health-seeking behavior in a culturally diverse setting. By using interviews, focus group discussions, and surveys, the study captured the perspectives of both caregivers and healthcare professionals, providing a well-rounded understanding of the cultural dimensions involved. Qualitative data were analyzed thematically, revealing cultural patterns and beliefs influencing caregiver decisions, while quantitative data were analyzed using descriptive and inferential statistics, allowing for a broader understanding of the prevalence and impact of these behaviors [3]. The theoretical framework of this study was grounded in constructivism and health-seeking behavior theories. Constructivism, which emphasizes the role of social and cultural context in shaping individuals’ perceptions and actions, was particularly relevant in understanding how caregivers interpret mental illness within their cultural frameworks. Health-seeking behavior theory provided a basis for analyzing how these interpretations translated into actual decisions regarding where and how to seek treatment [4]. The study targeted caregivers of individuals with mental illness from Uasin Gishu County and healthcare professionals working in the mental health unit of Moi Teaching and Referral Hospital (MTRH). MTRH, a key healthcare facility in Kenya, serves a large and diverse population, making it an ideal site for understanding the intersection between traditional beliefs and modern mental healthcare practices. This hospital-based setting provided a unique opportunity to explore the dynamics between culturally influenced health-seeking behaviors and the formal healthcare system [5]. Contemporary studies indicate that caregivers often face significant challenges in balancing cultural expectations with medical recommendations. In some instances, they may delay seeking hospital care or use it only after traditional methods fail to provide relief. This behavior is often rooted in deeply ingrained beliefs about the causes of mental illness, such as witchcraft, curses, or ancestral displeasure, which are more likely to be addressed by traditional healers than by medical professionals [6]. As a result, caregivers may exhibit health-seeking behaviors that are influenced by both cultural and social pressures, alongside concerns about the stigma associated with mental illness. The research highlights the need for healthcare providers to recognize and respect these cultural perspectives in order to provide more effective mental health interventions. By incorporating cultural sensitivity into their practice, healthcare professionals can better engage caregivers, improving trust and the likelihood of adherence to treatment [7]. Moreover, understanding the influence of cultural perspectives in health-seeking behavior can lead to the development of more inclusive mental health policies and programs that account for the cultural realities of the populations they serve.